2018
DOI: 10.1021/acssuschemeng.8b00234
|View full text |Cite
|
Sign up to set email alerts
|

Complete Oxidation of Methane on NiO Nanoclusters Supported on CeO2 Nanorods through Synergistic Effect

Abstract: Catalytic complete oxidation of CH4 at relatively low temperatures is significant for removing unburned CH4 from the exhaust of combustion engines fueled with natural gas or liquefied petroleum gas. Here a nanocomposite catalyst (NiO/CeO2) consisting of CeO2 nanorods and supported NiO nanoclusters was prepared by a two-step wet-chemistry method. This nanocomposite catalyst exhibits high catalytic activity for the complete oxidation of CH4 in the temperature range of 350–600 °C. A CH3-like intermediate bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 74 publications
(93 reference statements)
1
44
0
Order By: Relevance
“…As for NAP-XPS studies, C 1s spectra allowed the identification of a stable intermediate methyl species formed on the surface of Co 3 O 4 /CeO 2 during catalysis, which could be generated through dissociation of C−H of methane on Ce 4+ , Co 3+ or Co 2+ sites, since no oxygen vacancies were formed and detected on the cerium oxide support. Very similar results were obtained by Zhang and co-workers [141], who prepared CeO 2 nanorods with supported NiO nanoclusters of 10-12 nm average size and studied them under the same methane complete oxidation conditions as the work of Dou and colleagues [140]. Tracking the evolution of C 1s NAP-XPS features with increasing temperature under reaction conditions, they deduced the formation of a stable CH 3 -like intermediate bound to the Ni cation at 423−473 K. The generated surface CH 3 could be further activated to form CH 2 or even CH species, which in turn could combine with surface lattice oxygen atoms to form CO 2 and H 2 .…”
Section: Methane Partial and Complete Oxidationsupporting
confidence: 91%
“…As for NAP-XPS studies, C 1s spectra allowed the identification of a stable intermediate methyl species formed on the surface of Co 3 O 4 /CeO 2 during catalysis, which could be generated through dissociation of C−H of methane on Ce 4+ , Co 3+ or Co 2+ sites, since no oxygen vacancies were formed and detected on the cerium oxide support. Very similar results were obtained by Zhang and co-workers [141], who prepared CeO 2 nanorods with supported NiO nanoclusters of 10-12 nm average size and studied them under the same methane complete oxidation conditions as the work of Dou and colleagues [140]. Tracking the evolution of C 1s NAP-XPS features with increasing temperature under reaction conditions, they deduced the formation of a stable CH 3 -like intermediate bound to the Ni cation at 423−473 K. The generated surface CH 3 could be further activated to form CH 2 or even CH species, which in turn could combine with surface lattice oxygen atoms to form CO 2 and H 2 .…”
Section: Methane Partial and Complete Oxidationsupporting
confidence: 91%
“…6d shows four peaks at the binding energy of 856.4, 861.5, 873.1 and 880.2 eV attributed to Ni 2p 3/2 , satellite peak of Ni 2p 3/2 , Ni 2p 1/2 and the satellite peak of Ni 2p 1/2 , respectively. 35,36 The Ni a The specic toluene reaction rates over all the catalysts were calculated at 270 C. 2p XPS spectra primarily come from Ni foams. As for Co 2p XPS spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Deactivation of Ni/CeO 2 has been previously observed after CH 4 combustion reaction [26a,b] . For example, Zhang et al [26a] . showed that CeO 2 nanorods in Ni/CeO 2 catalysts significantly sintered after reacting at 600 °C, which was attributed to the low thermal stability of the CeO 2 nanorods.…”
Section: Introductionmentioning
confidence: 95%
“…Another challenge for CH 4 combustion reactions is catalyst deactivation via coke formation or metal sintering due to exposure to high temperatures (∼400‐700 °C) [26] . Deactivation of Ni/CeO 2 has been previously observed after CH 4 combustion reaction [26a,b] . For example, Zhang et al [26a] .…”
Section: Introductionmentioning
confidence: 95%